2019
DOI: 10.1104/pp.18.01495
|View full text |Cite
|
Sign up to set email alerts
|

PuHSFA4a Enhances Tolerance To Excess Zinc by Regulating Reactive Oxygen Species Production and Root Development in Populus

Abstract: Zinc (Zn) is an essential micronutrient but in excess is highly toxic to plants. Plants regulate Zn homeostasis and withstand excess Zn through various pathways; these pathways are generally tightly regulated by a specific set of genes. However, the transcription factors involved in excess Zn tolerance have yet to be identified. Here, we characterized a Populus ussuriensis heat shock transcription factor A4a (PuHSFA4a) that acts as a positive regulator of excess Zn tolerance in P. ussuriensis. We used overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 72 publications
0
43
0
Order By: Relevance
“…Many studies have revealed crosstalk between Hsfs, ROS and ROS-scavenging enzymes. In Populus ussuriensis, PuHSFA4a can increase glutathione S-transferase activity to reduce ROS production and improve Zn resistance of roots by directly regulating the target gene PuGSTU17 (Zhang et al, 2019). Transgenic Arabidopsis overexpressing maize ZmHsf06 can enhance salt tolerance by increases POD and SOD activities (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed crosstalk between Hsfs, ROS and ROS-scavenging enzymes. In Populus ussuriensis, PuHSFA4a can increase glutathione S-transferase activity to reduce ROS production and improve Zn resistance of roots by directly regulating the target gene PuGSTU17 (Zhang et al, 2019). Transgenic Arabidopsis overexpressing maize ZmHsf06 can enhance salt tolerance by increases POD and SOD activities (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we identified a PtHSFA4a from P. trichocarpa which is an ortholog of PuHSFA4a in P. ussuriensis 8 . Seven nucleotides in the sequences of PtHSFA4a were different from PuHSFA4a.…”
Section: Textmentioning
confidence: 90%
“…These genes include: Populus alba AQUA1, 4 A. thaliana AtHMA4, 5 A. thaliana AtMTP1 6 and Oryza sativa OZT1 7 . In P. ussuriensis, the heat shock transcription factor (PuHSFA4a) appears to confer excess Zn tolerance 8 . However, up to now transcription factors that regulate the Zn detoxification seldom characterized in plants.…”
Section: Textmentioning
confidence: 99%
See 1 more Smart Citation
“…To cope with heat stress, a set of defense mechanisms are activated to protect plants from the heat stressinduced damage, including the change of signal transduction and transcriptional regulation, the accumulation of osmolytes, the production of reactive oxygen species (ROS) scavenging enzymes, and the synthesis and accumulation of heat shock proteins (HSPs) [2,[5][6][7][8]. The generation and accumulation of ROS caused by heat stress can lead to the peroxidation of membrane lipids and proteins as well as carbohydrate oxidation and DNA damage [9,10]. To scavenge and detoxify ROS, plants have evolved both enzyme and non-enzyme systems [9].…”
Section: Read Full License Introductionmentioning
confidence: 99%